Time Management and Planning - Tony GIBEILY (Proche-Orient Études en management, 2020)
In late 2016, I launched a survey to which more than 300 Lebanese professionals of all walks answered. Its purpose was to learn more about the qualities / behaviors the Lebanese Professionals cherished the most. The survey gave rise to the publication of two articles in the past two years covering 1) the questions in it that related to the Qualities the Lebanese Professionals appreciated, as well as 2) the issues of Motivation and Personal Development.This is the third and last article based on the survey and that addresses the way the Lebanese Professionals appreciate the importance of Time and how they deal with its Planning.